Comparative reproductive effort and fecundity in the spider crabs, leurocyclus tuberculosus and libinia spinosa (Majoidea, Brachyura) - Gonzalez Pisani, Ximena (2014)
A comparative analysis of reproductive effort, fecundity, and egg weight was conducted in two species of spider crabs, Leurocyclus tuberculosus and Libinia spinosa, during one-year period. Ovigerous females were collected from Patagonia-Argentina (42°56′S, 64°21′W) and were measured (CW = carapace width). Each egg brood was weighed, dried and the number of eggs (F = fecundity) counted. Scatterplots of relative fecundity (RF = F/CW) were submitted to regression analyses. Mean F and RF was calculated for each season to assess seasonal variation of reproductive intensity. Mean F was 35,000 eggs in L. tuberculosus and 30,000 eggs in L. spinosa, with these values being intermediate in comparison with other Majoidea. The RF was approximately 18% higher in L. tuberculosus that presented an average dry weight egg 45% less than L. spinosa. Although in both species F showed a positive correlation with CW, less than the 20% of the variation in the number of eggs could be explained by female's size, suggesting there are other factors that influence F. The proportion of body energy devoted to reproduction (reproductive effort), exhibited significant differences between species. In Leurocyclus tuberculosus reproductive activity is significantly different along the 12-month suggesting that the conditions for 'optimal' egg production change throughout the year. In Libinia spinosa mean fecundity did not reveal significant differences over seasons. These results are central in studies of life-history theory and in the development of lifehistory models, as it is directly related to energy allocation and partitioning.